New record of Anelytra (Anelytra) eunigrifrons Ingrisch, 1998 (Orthoptera, Tettigoniidae: Conocephalinae, Agraeciini) from India - Nagar, Rajendra; Mal, Jhabar; Swaminathan, R. (Zootaxa, 2015)
The record of Anelytra (Anelytra) eunigrifrons Ingrisch, 1998 (Conocephlinae: Agraeciini) collected from Umiam in the North-east province, Meghalaya (India) is reported for the first time. Previously, the species was reported from Indo-China, Myanmar Burma, and Shan province, Carin Ghecu (Ingrisch, February 01, 1888 to March 31, 1888 and 1998). From India only one species, Anelytra (Anelytra) concolor Redtenbacher, 1891 has been recorded from Maharashtra, Mumbai. The paper includes the morphological characterization of the male of this species collected from North-east India.